2015
DOI: 10.1136/bmj.h6192
|View full text |Cite
|
Sign up to set email alerts
|

Is there a weekend effect in obstetrics?

Abstract: Accumulating evidence points to higher risks at the weekend for mothers and babies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Evidence has been found for [2][3][4][5][6][7][8][9][10] and against [2,11] disease-specific weekend effects, with conflicting results for stroke [12][13][14][15], acute myocardial infarction (AMI) [16][17][18][19], and hip fracture [20][21][22]. In previous studies, systematic reviews and meta-analyses, emergency patients admitted at the weekend suffered higher in-hospital mortality across both medical and surgical diagnoses [23][24][25][26][27], with a larger risk in major teaching hospitals [28,29], with varying specialty-specific [30][31][32][33][34][35][36] and disease-specific [26,[37][38][39][40] results. Emergency patients that were admitted at the weekend were found to have a 3-10 % higher risk than those admitted during the week [41,42], with those admitted at night on the weekend having a 14 % higher risk for in-hospital death [43].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has been found for [2][3][4][5][6][7][8][9][10] and against [2,11] disease-specific weekend effects, with conflicting results for stroke [12][13][14][15], acute myocardial infarction (AMI) [16][17][18][19], and hip fracture [20][21][22]. In previous studies, systematic reviews and meta-analyses, emergency patients admitted at the weekend suffered higher in-hospital mortality across both medical and surgical diagnoses [23][24][25][26][27], with a larger risk in major teaching hospitals [28,29], with varying specialty-specific [30][31][32][33][34][35][36] and disease-specific [26,[37][38][39][40] results. Emergency patients that were admitted at the weekend were found to have a 3-10 % higher risk than those admitted during the week [41,42], with those admitted at night on the weekend having a 14 % higher risk for in-hospital death [43].…”
Section: Introductionmentioning
confidence: 99%
“…Higher morbidity in hospitals during off-hours such as holidays and nighttime has been reported in numerous medical specialties. Studies have suggested that the obstetrics often encounter severe adverse neonatal events at nighttime 10 and on weekends 11 . In this study, we examined the monthly IVF outcome for fresh embryo transfer cycles retrospectively and found that the lowest monthly live birth rate resulted from procedures performed in January and February, apparently the CNY holiday season.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that obstetrics, in particular, are more likely to encounter severe adverse neonatal events during nighttime hours 10 and on weekends. 11 In this retrospective study, we investigated the monthly outcomes of fresh embryo transfer cycles in IVF and observed a decreased live birth rate during the CNY holiday season, particularly in the month of February. The reduction in live birth rate was significant, with a 15.1% lower rate in February compared to January.…”
Section: Discussionmentioning
confidence: 99%